2016
DOI: 10.32678/ijei.v7i2.41
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KEPUASAN MUZAKKI, TRANSPARANSI DAN AKUNTABILITAS PADA LEMBAGA AMIL ZAKAT TERHADAP LOYALITAS MUZAKKI (Studi Persepsi Pada LAZ Rumah Zakat)

Abstract: Abstract. The Influence of Muzakki Satisfaction, Transparency and Accountability in the Amil Zakat Institution toward Loyalty Muzakki (Perception Study on LAZ Rumah Zakat). This study aimed to analyze the effect of each variable that Muzakki satisfaction, transparency and accountability in the Amil Zakat Institution toward loyalty Muzakki. As a nonprofit organization, Lembaga Amil Zakat needs to pay attention the Muzakki satisfaction, transparency and accountability of institutions to increase loyalty Muzakki.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
1
15
0
10
Order By: Relevance
“…At least there are four novelties offered in this research. First, most of the previous studies analyzed the increase in zakat funds from the ZMO perspective (for examples, Coryna and Tanjung (2015); Triyawan and Aisyah (2016); Yuliafitri and Khoiriyah (2016); Yusrizal et al (2017); Yazid (2019); and Wahyudin et.al (2018), while this study directly examines from the perspective of the muzakki (Ikhwandha and Hudayati (2019). Second, this research emphasizes on profession zakat as ZMOs have not successfully managed it optimally (Astuti and Zulkifli (2018);Febriani and Siswajanty (2019).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At least there are four novelties offered in this research. First, most of the previous studies analyzed the increase in zakat funds from the ZMO perspective (for examples, Coryna and Tanjung (2015); Triyawan and Aisyah (2016); Yuliafitri and Khoiriyah (2016); Yusrizal et al (2017); Yazid (2019); and Wahyudin et.al (2018), while this study directly examines from the perspective of the muzakki (Ikhwandha and Hudayati (2019). Second, this research emphasizes on profession zakat as ZMOs have not successfully managed it optimally (Astuti and Zulkifli (2018);Febriani and Siswajanty (2019).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, transparency can minimize suspicion/negative perceptions (Inayah & Muanisah, 2018) and public distrust hence ZMO will gain trust from the community (Khasanah, 2010). Nasim andRomdhon (2014), Nurhayati et.al (2014), and Yuliafitri and Khoiriyah (Yuliafitri & Khoiriyah, 2016) found that ZMO transparency has a positive effect on muzakki loyalty. The consistency of these research results underlies the development of the following hypothesis: H1: Transparency in managing zakat funds at ZMO has a positive effect on muzakki's interest in distributing zakat.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Prinsip yang terakhir adalah keadilan (fairness) yang merupakan kesetaraan dalam memenuhi hak-hak dari stakeholders yang timbul dari perjanjian dan peraturan perundang-undangan yang berlaku (Labesi, 2013;Larasati et al, 2018). Sistem Good Corporate Governance menjadi penting untuk diterapkan dalam pengelolaan zakat yang baik pada lembaga Badan Amil Zakat Nasional (BAZNAS) (Atsarina, 2018;Yuliafitri & Khoiriyah, 2016), tidak terkecuali BAZNAS yang ada di kabupaten Kebumen.…”
Section: Pendahuluanunclassified
“…There are the needs of muzakki in the form of easy access to zakat institution, comprehensive zakat information, transparency, profesionalism, fatwas, satisfation, comfort, ease of giving zakat, and an environment that supports zakat [23]. there are also additional points of accountability and socialization in zakat [24], [25], [26]. On the other hand, muzakki need the image and reputation of zakat institutions as trust in zakat, how to handle complaints from zakat institutions, service ethics, service provision, transparency [27], provision of mustahik allevation programs that are not only distribution zakat without any purpose of allevation, zakat reports, socialization of zakat benefits, communication and relationship from zakat institution to muzakki, as well as organizational fanaticism by muzakki related to zakat institutions [28].…”
Section: Muzakkimentioning
confidence: 99%